ANALYTICAL SOLUTION OF PARTIAL TASKS OF SHEAR WAVE IN A CYLINDRICAL LAYER (in the case of the constant values γ-α + 2 = 0 and α = β) - Larissa Kainbaeva; Kanibaikyzy Kundyzay; Smakhanova Aizhan Korganbekovna; Taimuratova Lidiya Ungarbaevna (Academic Scientific Journal of Computer Science, 2019)
The concept of phase velocity is introduced as the rate of change of the phase medium in studies of shear wave processes of circular elements in deformable bodies. In the case of harmonic oscillations of a cylindrical shell, the phase velocity is expressed in terms of the frequency of natural vibrations freely supported along the edges of the shell, and therefore, the study of waves in a cylindrical layer is most directly related to the problem of determining the natural forms and vibration frequencies of shells of finite length. The results of this work on onedimensional cylindrical waves in elastic and viscoelastic media and rods allow us to study the influence of the characteristics of the material of the media on the wave fields in the material. The problems of the theory of viscoelasticity have recently attracted the special attention of many researchers and engineers in connection with the use of polymer materials in various industries.